Memahami Dunia Anak Melalui Puisi di dalam Tabloid Lintang - Sudewa, I Ketut (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 20 No 1 (2020), 2020)
Children express their feelings and thoughts in literary works (poetry) that are created naturally and honestly. They express their world in a beautiful and happy way. Therefore, it is important to understand the world of children expressed in the literary works they create. In this study, discussed about the world of children depicted in children's poetry published in the Lintang tabloid published in January to November 2017. The problems discussed are (1) how the child's world image in poetry contained in the Lintang Tabloid; and (2) how children express their world through poetry in the Lintang tabloid. The method used is a qualitative method that focuses on library studies with techniques of reading, listening, note taking, and interpretation. The theory used is semiotic theory. The results showed that the children's poetry in the Lintang Tabloid published in the Lintang tabloid published in January to November 2017 generally contained five themes, namely: the environment, animals or animals, profession, plants, and love of the motherland. All these themes are expressed with the feelings and thoughts of the child's world and dominantly expressed by using the language style of repetition, metaphor, and personification.